2019
DOI: 10.1038/s42255-018-0009-4
|View full text |Cite|
|
Sign up to set email alerts
|

Slc12a8 is a nicotinamide mononucleotide transporter

Abstract: Nicotinamide mononucleotide (NMN) is a biosynthetic precursor of NAD + known to promote cellular NAD + production and counteract age-associated pathologies associated with a decline in tissue NAD + levels. How NMN is taken up into cells has not been entirely clear. Here we show that the Slc12a8 gene encodes a specific NMN transporter. We find that Slc12a8 is highly expressed and regulated by NAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
164
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(193 citation statements)
references
References 48 publications
11
164
0
Order By: Relevance
“…Unfortunately, we failed to detect NMN in plasma samples in this study, most likely because freezing plasma samples before extraction might have caused the degradation of NMN. The procedure of blood sampling could have also contributed to the failure of the detection of NMN, because the recent reports showed that NMN was degraded very rapidly in blood that was handled above -80°C [7,21]. There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Unfortunately, we failed to detect NMN in plasma samples in this study, most likely because freezing plasma samples before extraction might have caused the degradation of NMN. The procedure of blood sampling could have also contributed to the failure of the detection of NMN, because the recent reports showed that NMN was degraded very rapidly in blood that was handled above -80°C [7,21]. There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have already reported that NMN restores tissue NAD + levels and ameliorates obesity, insulin resistance, muscle mitochondrial dysfunction, renal failure, and retinal degeneration in rodent models [3][4][5][6]. Moreover, it was recently reported that NMN was rapidly absorbed through a transporter in the small intestine [7]. Although preclinical results provide a hope to develop NMN as an evidence-based anti-aging intervention, the safety and efficacy of NMN in humans remain unclear.…”
mentioning
confidence: 99%
“…On the other side, NMN can be also used by CD73, which generates nicotinamide riboside (NR) (66,70), that, likely through equilibrative nucleoside transporters (ENTs), can be imported as NAD precursor (71,72) (Figure 1). Recently, Slc12a8 was identified as specific NMN transporter (73), suggesting that NMN can be internalized without conversion to NR. Studies on cell type expression pattern of this transporter will clarify this possibility.…”
Section: Extracellular Nad and Its Biological Rolementioning
confidence: 99%
“…There is no consensus on how NMN is transported to the cell (Grozio et al, 2019;Schmidt and Brenner, 2019) (Table 2). However, NR is five times more effective than NMN in increasing intracellular NAD + levels in skeletal muscles (Oakey et al, 2018) (Table 2).…”
Section: Precursors Of Nad +mentioning
confidence: 99%
“…-One of the most used -Has shown an increase in NAD + levels in the cell -No consensus on how is transported to the cell Nikiforov et al, 2011;Grozio et al, 2019;Schmidt and Brenner, 2019 Nicotinamide (NAM) Can be a stimulator in cells Smaller increase in NAD + compared to NR Cantó et al, 2012 Nicotinamide riboside (NR) -Action on mammalian cells -Minimal toxicity -High bioavailability -High capacity to cross the blood-brain barrier -Supports neuronal NAD + synthesis -Greater ability to stimulate a significant increase in NAD + levels and intermediate precursors No evidence Yang H. et al, 2007;Bogan and Brenner, 2008;Cantó et al, 2012;Trammell et al, 2016;Airhart et al, 2017;Martens et al, 2018 resistance against OS and prevents cell death due to the protective function of SIRT3 (Hafner et al, 2010), which stimulates SOD, responsible for enhancing the "detoxification" of ROS (Chen et al, 2011) (Figure 2). Supplementation with NR is safe in mice and humans and has minimal toxicity, high bioavailability and high capacity to cross the blood-brain barrier (Trammell et al, 2016;Airhart et al, 2017;Martens et al, 2018) (Table 2).…”
Section: Precursors Of Nad +mentioning
confidence: 99%